2018
DOI: 10.2147/imcrj.s178816
|View full text |Cite
|
Sign up to set email alerts
|

Renal cell carcinoma presenting as nonspecific gastrointestinal symptoms: a case report

Abstract: BackgroundRenal cell carcinoma (RCC) arises from the renal epithelium and accounts for more than 90% of kidney cancers. RCC has a diverse range of clinical manifestations. The classical triad of loin pain, hematuria and abdominal mass is only present in 4%–17% of cases. Here, we demonstrate a unique case of RCC presenting as upper gastrointestinal (GI) symptoms without any specific GI involvement.Case presentationA 49-year-old man, presented with ongoing severe heartburn, nausea and vomiting for 5 months. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Though RCC does not have a propensity for gastrointestinal metastasis, there are several reports of its metastasis to the gastrointestinal tracts in humans [21,22].Third, apart from physical compression or embolus formation from metastasis, RCCs may attribute to the incidence of IL, which is associated with either the functional alteration of kidney or pathological conditions due to the RCC itself. Albeit uncommon, it has been reported that RCC can be associated to gastrointestinal diseases [23]. RCC is associated with gastrointestinal symptoms such as pain, gastritis, and hiatus hernia [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though RCC does not have a propensity for gastrointestinal metastasis, there are several reports of its metastasis to the gastrointestinal tracts in humans [21,22].Third, apart from physical compression or embolus formation from metastasis, RCCs may attribute to the incidence of IL, which is associated with either the functional alteration of kidney or pathological conditions due to the RCC itself. Albeit uncommon, it has been reported that RCC can be associated to gastrointestinal diseases [23]. RCC is associated with gastrointestinal symptoms such as pain, gastritis, and hiatus hernia [23].…”
Section: Discussionmentioning
confidence: 99%
“…Albeit uncommon, it has been reported that RCC can be associated to gastrointestinal diseases [23]. RCC is associated with gastrointestinal symptoms such as pain, gastritis, and hiatus hernia [23]. Additionally, other renal diseases such as hemolytic uremic syndrome have been associated with the incidence of IL [24].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of kidney cancer varies across countries. Kidney cancer is most common diagnosed in people over 75 years old with the highest rates of diagnosis between 85 to 89 years old for both males and females [ 1 , 2 ]. Renal cell carcinoma (RCC), also known as hypernephroma, is currently the most common type of renal tumor found in adults aged between 50 to 70 years old [ 3 ].…”
Section: ⧉ Introductionmentioning
confidence: 99%